Addressing the Addressee: Shakespeare and Early Modern Epistolary Theory - Kerry Gilbert-Cooke (Journal of Early Modern Studies, 2014)
Considering the emergence of epistolary theory in mid-sixteenth-century England, its value and function, the article attempts to show how these theories helped to construct, in contemporary correspondence, the addressee’s identity. One of the most important precepts was, as Angel Day states in his manual The English Secretorie, that, when composing a letter, writers tailored their text to the addressee. Even invented letters in Shakespeare’s plays reveal that, while correctly addressing the addressee does not necessarily guarantee success, address was considered the most important tool at the writer’s disposal when attempting to secure the addressee’s good will. Importantly, the observance of this precept even in drama indicates that epistolary theory had a more pervasive influence in early modern England than previously thought.